Enhancement of oxidation of dimethyl ether through formation of hybrid electrocatalysts composed of Vulcan-supported PtSn decorated with Ru-black or PtRu nanoparticles. (20th December 2021) - Rutkowska, Iwona A.; Rytelewska, Beata; Kulesza, Pawel J.
Highlights: Vulcan-supported PtSn are decorated with Ru-black or bimetallic PtRu nanoparticles. Thus prepared hybrid catalysts exhibit high activity toward dimethyl ether oxidation. Ru supports activity of Sn in oxidative removal of poisoning adsorbates on Pt sites. PtRu-decorated Vulcan-supported PtSn shows high activity for methanol oxidation. Abstract: Electrocatalytic activity of Vulcan-supported PtSn (PtSn/C) nanostructured alloys toward electrooxidation of dimethyl ether (DME), a potential small-organic-molecule fuel, has been significantly enhanced in acid medium (0.5 mol dm −3 H2 SO4 ) by decorating PtSn/C with ruthenium black or bimetallic PtRu nanoparticles. The enhancement effect concerns both shifting the onset potential for the DME-oxidation toward less positive values and increase of the DME electrocatalytic current densities recorded under both cyclic voltammetric and chronoamperometric conditions. The activating capabilities of ruthenium nanostructures seem to originate from the existence of reactive ruthenium oxo/hydroxo groups (even below 0.45 V vs. RHE) on their surfaces capable of inducing the oxidative removal of poisoning (CO-type) adsorbates from the neighboring platinum catalytic sites. In that respect, the Ru-oxo species originating from Ru or PtRu additives seem to support activity of Sn cocatalytic sites interacting with Pt within the PtSn heterogenous alloy. The Ru-decorated PtSn/C and, in particular, PtSn/C admixed with PtRu exhibit very high activity toward the oxidation of methanol which is also an important DME-oxidation intermediate. On the whole, the hybrid materials composed of Vulcan-supported PtSn decorated with Ru or PtRu nanoparticles seem to act as multifunctional nanoreactors inducing not only oxidative stripping of poisoning adsorbates but also catalyzing oxidation of the DME-reaction intermediates (methanol).